Upaya untuk Meningkatkan Kemampuan Guru dalam Pemanfaatan Media Microsoft Powerpoint pada Mata Pelajaran SKI di MI NU Rawa Bening - Tri Ratna Dewi; Nesi Anti Andini; Miftakhur Rohmah (Jurnal Indonesia Mengabdi, 2019)
Teachers are the drivers of education, in the digital era teachers are required to renew learning by utilizing existing technology with the aim of not lagging behind the times. The facts in the field show that conditions are of concern, the use of technology is still not optimal. This is due to the lack of facilities that support the development of learning technology and also the human resources that control the technology are also minimal. This training aims to provide training by presenting some material related to the development of interactive learning media, namely Microsoft Power Point so that the implementation of SKI learning at Rawabening MI schools does not seem monotonous so as to increase interest and quality of learning among students. The coaching process delivered by the servants who acted as instructors and tutors took place conducively. Material designed in such a way by servants can be understood, understood and well understood by the participants. This was evident from the enthusiasm of the participants who participated in the training actively communicating with the speaker, so that the training was carried out well and interactively.